Acute physical exercise increases leptin-induced hypothalamic extracellular signal-regulated kinase1/2 phosphorylation and thermogenesis of obese mice - Gaspar, Rafael Calais; Muñoz, Vitor Rosetto; Kuga, Gabriel Keine [UNESP]; Nakandakari, Susana Castelo Branco Ramos; Minuzzi, Luciele Guerra; Botezelli, José Diego; da Silva, Adelino S.R.; Cintra, Dennys Esper; de Moura, Leandro Pereira; Ropelle, Eduardo Rochete; Pauli, José Rodrigo (Wiley, 2018)
The obesity is a result of energy imbalance and the increase in thermogenesis seems an interesting alternative for the treatment of this disease. The mechanism of energy expenditure through thermogenesis is tightly articulated in the hypothalamus by leptin. The hypothalamic extracellular signal-regulated kinase-1/2 (ERK1/2) is a key mediator of the thermoregulatory effect of leptin and mediates the sympathetic signal to the brown adipose tissue (BAT). In this context, physical exercise is one of the main interventions for the treatment of obesity. Thus, this study aimed to verify the effects of acute physical exercise on leptin-induced hypothalamic ERK1/2 phosphorylation and thermogenesis in obese mice. Here we showed that acute physical exercise reduced the fasting glucose of obese mice and increased leptin-induced hypothalamic p-ERK1/2 and uncoupling protein 1 (UCP1) content in BAT (P < 0.05). These molecular changes are accompanied by an increased oxygen uptake (VO 2) and heat production in obese exercised mice (P < 0.05). The increased energy expenditure in the obese exercised animals occurred independently of changes in spontaneous activity. Thus, this is the first study demonstrating that acute physical exercise can increase leptin-induced hypothalamic ERK1/2 phosphorylation and energy expenditure of obese mice.
Keywords: brown adipose tissue (BAT); extracellular signal-regulated kinase-1/2 (ERK1/2); hypothalamus; obesity; physical exercise; thermogenesis; UCP1